Sosiodemografi dan Pemantauan Klinik Secara Mandiri Penyandang Diabetes Mellitus Tipe II di RSUD dr. Doris Sylvanus Palangkaraya - Nurhalina Nurhalina; Dwi Purbayanti; Suratno Suratno; Syahrida Dian Ardhany (Borneo Journal of Medical Laboratory Technology, 2020)
In Central Kalimantan province efforts to manage type 2 diabetes millitus have been undertaken to reduce the prevalence of case and risk factors. Based on the results of Riskesdas 2013.Medical records of Doris Sylvanus Hospital in 2015, the number of diabetes millitus patients has increased from 375 cases in 2014 and 514 cases in 2015. The purpose of this study was to determine the sociodemographic and clinical monitoring independently by people with type 2 diabetes mellitus. Design studyis ovbservasional with descriptive approach were population is people with type 2 diabetes millitus who visited Dr.Doris Sylvanus Palangka Raya hospitaland had been diagnosed for more than 1 year. Data were collected through direct interviews with respondents and medical records of respondents.The results showed thatthe majority of respondents were more than 50 years old (76%), female (59%), were married (91.8%), worked as civil servants / police / military (37.2%) and did not work (27.9%). based on the length of diagnosis, the majority have been diagnosed for more than 3 years (63.4%).The average independent clinical monitoring of respondents for their health condition was 41.05% and there were 57.65% of respondents who did not conduct routine health monitoring. The results also showed that 100% of respondents did not monitor neuropathy and monitor erectile dysfunction. Whereas respondents who monitor HbA1c are only around 1.1%